1993
DOI: 10.1111/j.1525-1446.1993.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness, Depression, and Social Support of Patients with COPD and Their Spouses

Abstract: Thirty clients with chronic obstructive pulmonary disease (COPD) and their spouses were interviewed to examine differences in the relationships among loneliness, depression, and social support. Data were collected during structured in-home interviews using the UCLA loneliness scale, the Center for Epidemiological Studies depression scale, and the social support questionnaire. The clients and spouses did not differ significantly on measures of loneliness and depression, with mean scores for both groups higher t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
50
3
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(58 citation statements)
references
References 37 publications
3
50
3
2
Order By: Relevance
“…Previous research [5] found that COPD patients who were dissatisfied with their social relationships were likely to be lonely and depressed. This study supported that finding, in that higher levels of positive social support predicted lower levels of depression.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous research [5] found that COPD patients who were dissatisfied with their social relationships were likely to be lonely and depressed. This study supported that finding, in that higher levels of positive social support predicted lower levels of depression.…”
Section: Discussionmentioning
confidence: 96%
“…The more extensive work in other chronic illnesses, such as rheumatoid arthritis, cancer and chronic pain, has demonstrated that coping strategies, self-efficacy and social support predict adjustment to illness. The small number of studies investigating the relationship between psychological variables and indices of adjustment for patients with COPD, suggest that the role of coping strategies [3], levels of self-efficacy [4] and social support [5], in predicting adjustment warrants further investigation. LAZARUS and FOLKMAN [6] propose a cognitively oriented theory of stress and coping, which has had a great impact on the chronic illness literature.…”
mentioning
confidence: 99%
“…Although families of inpatients reported good levels of mutuality, this may, in a family of a severely ill patient, imply enmeshment, and a patient's significant other may have had to unwillingly assume the responsibility for nursing an ill spouse. 21 Home oxygen therapy patients have to plan their daily activities carefully and avoid mentally stressful situations. Strict routines in patients' lives cause changes in families' lives.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with patients suffering from terminal lung cancer, health-related quality of life in COPD is even worse (Gore et al 2000;Habraken et al 2009). The patients' disease also impacts their partners' well-being and quality of life (Bergs 2002;Cannon and Cavanaugh 1998;Grant et al 2012;Hynes et al 2012;Kanervisto et al 2007a; Kanervisto et al 2007b;Keele-Card et al 1993;Rees et al 2001;Sexton and Munro 1985). Spouses' health-related quality of life is considerably lower compared to samples similar in age (Kühl et al 2008;Thöne et al 2011), and it tends to be even lower than patients' quality of life (Rees et al 2001).…”
Section: Introductionmentioning
confidence: 95%